The function of CD164 in breast cancer and its possibility as a molecular biomarker: bioinformatics analysis and experimental validation - Li, Mengxin; Mao, Juanjuan; Wang, Guang; Chen, Jiasi; Hong, Jinghui; Wang, Xue; Liang, Baoling; Song, Dong (Frontiers in Immunology, 2025)
BackgroundBreast cancer is the most prevalent malignancy among women globally. Molecular-targeted therapy improves treatment efficacy by precisely targeting tumor-specific molecules, minimizing damage to healthy tissues. Identifying new molecular targets is essential for enhancing therapeutic outcomes and prognosis in breast cancer.MethodsThe TCGA database was used to assess CD164 expression in breast cancer and its correlation with prognosis. Chemosensitivity analysis was performed to evaluate the association between CD164 and response to targeted therapies. Immune infiltration analysis was conducted to assess the relationship between CD164 expression and immune cell populations. CCK-8 assays, clonogenic assays, and flow cytometry analyses were employed to examine the effects of CD164 knockdown on cell viability, proliferation, cell cycle progression, and apoptosis. RNA sequencing and Gene Set Enrichment Analysis (GSEA) were performed to identify pathways regulated by CD164.ResultsCD164 was highly expressed in breast cancer tissues and correlated with poorer prognosis, including shorter disease-free and overall survival. Chemosensitivity analysis linked CD164 to sensitivity to multiple targeted therapies, suggesting its role in oncogenic pathways. Immune infiltration analysis revealed CD164’s association with immunosuppressive cells, including resting CD4 memory T cells, M2 macrophages, and mast cells, while exhibiting a negative correlation with Tregs and NK cells, underscoring its significance in the immunosuppressive tumor microenvironment. CD164 knockdown inhibited cell viability and proliferation and induced cell cycle arrest and apoptosis. RNA sequencing and GSEA showed that CD164 regulates proliferation, metabolism, migration, and adhesion pathways while suppressing tumor-promoting pathways and activating immune-related pathways.ConclusionsCD164 plays a critical role in breast cancer progression, influencing tumor growth, immune evasion, and therapeutic response. It represents a promising therapeutic target, offering potential for improving breast cancer treatment and prognosis.